Labouring the Canadian Millennium: Writings on Work and Workers, History, and Historiography - Palmer, Bryan D. (Past CCLH Publications, 2000)
As Canadian workers, the labour movement, and scholars confront a new millennium, new opportunities and new challenges loom large. This volume, which mirrors Labour/Le Travail Volume 46, commissions a number of articles addressing themes that will be of consequence as we enter the 21st century. The articles that appear in this collection are authored by some of the more prominent social scientists working in the field of labour-related studies, among them Desmond Morton, Ian McKay, Joan Sangster, Cynthia Comacchio, David Frank, and Jacques Rouillard. Their writing appears in the book, grouped in a series of thematic sections: institutions and ideas; gender, sexuality and family; Quebec and the national question; culture; and workers and the state. Topics such as Canadian socialism, pivotal events such as the 1949 Asbestos strike, and important cultural undertakings, such as working-class representations on film and video, are addressed. Historiographical controversies and debates associated with the relations of women’s and working-class histories or different generational styles associated with the presentation of labour’s past are surveyed. This is an issue all interested in Canadian society and its development will not want to miss. --Publisher's description
Keywords: Canada; History; History. Labor movement; History. Working class; Labor; Labor movement; Working class